Comparison of the Mechanical Properties and Forming Behavior of Two Texture-Weakened Mg-Sheet Alloys Produced by Twin Roll Casting - Victoria-Hernández, José; Yi, Sangbong; Klaumünzer, David; Letzig, Dietmar (Frontiers in Materials, 2019)
The influence of rolling and annealing on the resulting mechanical properties and forming behavior of Mg-Zn-RE and Mg-Zn-Ca alloys produced via twin roll casting is investigated. After hot rolling followed by an annealing treatment, both alloys develop a fine-grained microstructure with average grain sizes less than 10 µm. A distinctive development of a texture with a pronounced split of the basal poles in the transverse direction, so called TD-split, is observed in both alloys during the annealing. Due to the fine microstructure and weak texture, which enhances the activation of basal slip, both alloys show large ductility with fracture strain higher than 30%. However, due to the TD-split texture, a high asymmetry of the yield stress is observed, where the yield stress in rolling direction is significantly higher than the yield stress along 45° and the transverse direction. Both alloys show high stretch formability at room temperature with Erichsen indices around 7. Despite a low planar anisotropy and high stretch formability, the Mg-Zn-RE alloy shows undesirable earing behavior, while the Mg-Zn-Ca alloy fractures during warm deep drawing. Moreover, the deep drawing operation using the as-rolled sheet of Mg-Zn-RE alloy can be successfully done. It is observed that the earing behavior can be effectively reduced by deviating from the TD-split texture. In this regard, cold rolling was explored to reduce the anisotropy of the ductile and formable alloy.